Explore customers' needs in the process of developing high-tech services - Bui, Thanh Van (2013)
The project Unelma is implemented in the cooporation between Finnish and Swedish Universities aims to create novel high-tech services and working operational concepts. It concentrates on the development of imaging and analyzing to improve new materials and products from macroscopic scale (~centimeters) to Nano scale (~nanometers. The purpose of the project is to enforce the cross-border R&D cooperation in the Northern Finland, Sweden and Norway as well as lay the ground for fruitful collaboration among industrial organizations. In the spring period, the research has been implemented by Oulu University of Applied Sciences (OUAS) in order to explore the real need that the service provider desires. The service provider is Microscopy and Nanotechnology Centre (MNT). The study aims to find out what the service provider’s true difficulties by utilizing service design tools and survey method. Altogether, the researches were carried out in spring term from March to June 2013. The results of the study indicate that selection research method is very important and experiential activities are effective than other methods. Additionally, the study figured out that the service provider needs better advertising and marketing strategies the most. In accordance to pragmatic method contribution, new recommendation for the further research is to carry out face-to-face survey to ensure the responds and obtain correct answers. The results of the research may be developed further to explore the service customers in the process of creating the high-tech service process suitably and perfectly.